EDUCATION AND THE DIGITAL REVOLUTION: STRATEGIES FOR ENHANCING INTELLIGENCE IN THE INFORMATION AGE - Sri Hastuti; Hayyatun Mawaddah; Kasmudin Mustapa (International Journal of Teaching and Learning, 2025)
This research investigates the impact of the digital revolution on education and how adaptive and integrative strategies can be applied to enhance intelligence during the information age. Through the literature research method, this study examines various scholarly sources and publications according to the research context. The results show that the integration of technology in education provides opportunities for wider access to knowledge and supports continuous learning. However, challenges such as the digital divide must be overcome to ensure that all students can benefit from digitally enhanced education. Adaptive strategies involving flexible curricula and teaching responsive to technological developments were shown to improve students' ability to think critically, creatively and collaboratively. The implication is that education systems should encourage learning methodologies that foster continuous customization and integration to equip students with the skills needed for success in an ever-evolving knowledge-based society.